Diversity in Unity. The European Union and Member States Emergency Aid to the Countries of the Middle East and North Africa (MENA) Region - Fulvio Attinà (Romanian Journal of European Affairs)
This paper draws the attention of the EU foreign policy professionals and researchers community towards the aid policy of the European Union and the major Member States towards the countries affected by humanitarian emergencies and disasters. The determinants and vertical coherence of this policy are put under observation. In particular, by measuring and comparing financial aid to the countries of the Middle East and North Africa, the MENA region, the present study assesses the importance of the aid policy vertical coherence. The analysis of the data supports the mainstream view about the common values and goals of the foreign aid policies of the Union and the Member States but warns about coherence between the Union and the state level as the European countries’ aid allocation to the MENA countries is apparently driven by different priorities.